Environmental psychology an introduction - Steg, Linda; van den Berg, Agnes E.; de Groot, Judith I. M. (Chichester, West Sussex British Psychological Society, 2013)
"Explores the environment's effects on human wellbeing and behaviour, factors influencing environmental behaviour and ways of encouraging pro-environmental action"--Provided by publisher.
Keywords: Environmental psychology